2014
DOI: 10.1039/c4cc02878c
|View full text |Cite
|
Sign up to set email alerts
|

A biotin-guided fluorescent-peptide drug delivery system for cancer treatment

Abstract: Herein, we present a fluorescent-peptide drug delivery system composed of biotin-naphthalimide-HJ inhibitor peptide2, prodrug 1. Treatment of 1 to biotin receptor-positive HepG2 cells, which are resistant to high concentrations of the HJ inhibitor peptide2, decreased cell viability and increased intracellular fluorescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 27 publications
0
38
0
Order By: Relevance
“…The varied uptake level of Bio-cage@Ru in different cells should be attributed to their different expression level of biotin receptors[42][43][44]. To further demonstrate the role of biotin/receptor-mediated targeting on the selective uptake of Bio-cage@Ru, we used excess biotin to block biotin receptors on HepG2 cells and determined the uptake efficiency of Biocage@Ru in HepG2 cells.…”
mentioning
confidence: 99%
“…The varied uptake level of Bio-cage@Ru in different cells should be attributed to their different expression level of biotin receptors[42][43][44]. To further demonstrate the role of biotin/receptor-mediated targeting on the selective uptake of Bio-cage@Ru, we used excess biotin to block biotin receptors on HepG2 cells and determined the uptake efficiency of Biocage@Ru in HepG2 cells.…”
mentioning
confidence: 99%
“…5). 15 Holliday junction (HJ) inhibitor peptide 2 was used as a model peptide drug that shows promise as an antimicrobial and anticancer agent. To investigate the role of the biotin within the conjugate, both biotin-receptor-positive HepG2 cells and biotin-receptor-negative W138 cells were treated with 6 .…”
Section: Design Of Targeted Fluorescent Prodrug Conjugatesmentioning
confidence: 99%
“…Biotin, also known as vitamin H, is able to target the tumors by attaching to the SMVT receptors in tumor cells. 17,18,[20][21][22] As a water-soluble drug, DOX$HCl can hardly be encapsulated by PLGA NPs via hydrophobic interaction, so the desalted process was prerequisite to transform the hydrophilic drug to hydrophobic drug. Because triethylamine was a volatile weak base, the DOX could escape from being destroyed and the excess of triethylamine would be easily evaporated.…”
Section: Preparation Of the Npsmentioning
confidence: 99%
“…20 Profoundly, it has been reported that SMVT transporters are overexpressed in many tumor cells including HepG2 cells. [21][22][23] Thus, the cell experiments in this study were exerted on HepG2 cells.…”
Section: Introductionmentioning
confidence: 99%